1987
DOI: 10.1172/jci113208
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus infection in human arterial cells. Implications in arteriosclerosis.

Abstract: Herpesviruses have been implicated as etiologic factors in the pathogenesis of human arteriosclerosis. We have examined the pathobiological effects of human herpes simplex virus (HSV-1) infection in influencing lipid accumulation and metabolism in human and bovine arterial smooth muscle cells (SMC). Significantly greater amounts of saturated cholesteryl esters (CE) and triacylglycerols (TG) accumulate in HSV-Iinfected human and bovine arterial SMC than uninfected cells. This CE accumulation results, in part, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 15 publications
3
59
0
2
Order By: Relevance
“…Although both groups exhibited a marked increase in cholesterol esters and triacylglyceride compared with the mock-infected group with 3-week cholesterol feeding, they also showed great standard deviation in triacylglyceride levels, reflecting individual differences in responding to the given insults. The result agrees with previous studies showing that cholesterol ester accumulation in cultured smooth muscle cells was stimulated by the infection of human herpes simplex virus type 1 (Hajjar et al, 1986;Hajjar et al, 1987). It is also noteworthy that the lipid composition of aortic lesions after virus infection and 6-week cholesterol feeding exhibited a striking similarity to those reported in the type II lesions of human atherosclerosis (Geer and Malcom, 1965;Insull and Bartsch, 1966).…”
Section: Discussionsupporting
confidence: 92%
“…Although both groups exhibited a marked increase in cholesterol esters and triacylglyceride compared with the mock-infected group with 3-week cholesterol feeding, they also showed great standard deviation in triacylglyceride levels, reflecting individual differences in responding to the given insults. The result agrees with previous studies showing that cholesterol ester accumulation in cultured smooth muscle cells was stimulated by the infection of human herpes simplex virus type 1 (Hajjar et al, 1986;Hajjar et al, 1987). It is also noteworthy that the lipid composition of aortic lesions after virus infection and 6-week cholesterol feeding exhibited a striking similarity to those reported in the type II lesions of human atherosclerosis (Geer and Malcom, 1965;Insull and Bartsch, 1966).…”
Section: Discussionsupporting
confidence: 92%
“…20 Herpesvirus infection increases aortic lipid accumulation by 2-3-fold in smooth muscle cells of chickens in vitro as well as in vivo. [21][22][23] Cholesterol uptake by the smooth muscle cells infected with Herpes simplex virus is associated with increased activity of LDL receptor, and reduced hydrolysis and efflux of cholesterol esters. 24 Moreover, Feingold et al 25 showed increased hepatic lipid and cholesterol synthesis in mice injected with various cytokines such as tumor necrosis factor alpha, interleukin-1 and interferon gamma.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood that pathogen burden is not just a surrogate marker for some other factor or factors is suggested by the extremely high risk posed (Table 3) and the many mechanistic studies that demonstrate pathogens evoke cellular changes that in themselves could account for the development of atherogenesis and for the precipitation of the acute complications of atherosclerosis. [22][23][24] One potential confounding influence not evaluated in the present study that could influence our conclusions is the impact of socioeconomic status (SES). Unfortunately, we cannot address this issue definitively because information related to SES was not obtained as part of the database.…”
Section: Zhu Et Al Multiple Infections and MI Or Deathmentioning
confidence: 99%